Challenges of integrating war displaced persons from Kindu in the DRC after the wars - Makinga, Alphonse Sabiti; Spartacus, KABALAMUNYEMO (IJRDO - Journal of Social Science and Humanities Research, 2025)
This paper analyzes and outlines the main integration challenges faced by war-deplaced people from Kindu in the DRC more than 10 years after the war.